2020
DOI: 10.21203/rs.3.rs-42771/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding COVID-19 nonlinear multi-scale dynamic spreading in Italy

Abstract: The outbreak of COVID-19 in Italy took place in Lombardia, a densely populated and highly industrialized northern region, and spread across the northern and central part of Italy according to quite different temporal and spatial patterns. In this work, a multi-scale territorial analysis of the pandemic is carried out using various models and data-driven approaches. Specifically, a logistic regression is employed to capture the evolution of the total positive cases in each region and throughout Italy, and an en… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…With the aim of taking into account the undetected infected, our model includes more compartments than a standard SIRD. In the same spirit of our work, other authors proposed compartmental models allowing for the presence of undetected asymptomatic individuals in the population [9][10][11][12][13][14][15]. Calafiore and colleagues [12] resort to a standard SIRD model and take into account the undetected infected individuals assuming that they represent a fixed fraction of the notified ones, as we do.…”
Section: Comparison With Similar Modelsmentioning
confidence: 95%
See 2 more Smart Citations
“…With the aim of taking into account the undetected infected, our model includes more compartments than a standard SIRD. In the same spirit of our work, other authors proposed compartmental models allowing for the presence of undetected asymptomatic individuals in the population [9][10][11][12][13][14][15]. Calafiore and colleagues [12] resort to a standard SIRD model and take into account the undetected infected individuals assuming that they represent a fixed fraction of the notified ones, as we do.…”
Section: Comparison With Similar Modelsmentioning
confidence: 95%
“…In order to express a greater belief in the deaths counts, rather than in the observed notified infections, which are more prone to registration errors, false positives (albeit probably negligible) or delays, we a priori set w 1 = 0.6 and w 2 = 0.4 [11].…”
Section: Model Identifiability and Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…susceptibles, exposed, symptomatic infectives, asymptomatic infectives, susceptibles in quarantine, exposed in quarantine, hospitalized, recovered) has been introduced to estimate the risk of transmission of the novel coronavirus [3] , [4] and to evaluate the effectiveness, even in the long period, of control measures against epidemic [5] , [6] . The role played by asymptomatic individuals was widely stressed, recognizing how a prompt isolation of asymptomatic infectives would change the dynamics of Covid19 spread [7] , [8] , [9] . In particular, the impact of not officially documented cases on the spread of the novel Coronavirus epidemic was recognized to be enormous since, without the transmission due to the undocumented cases, the number of confirmed infections would have been far less in the whole of China with an estimated decrease of about 80 % [10] .…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…Saha et al [12] proposed an SEIRS epidemic model to explore coronavirus infection and suggested that susceptible individuals can avoid infection by taking appropriate precautions. Quaranta et al [13] performed a multi-scale dynamic analysis of COVID-19 outbreak in Italy to show changes at different geographic scales. Leung et al [14] established a susceptible-exposedinfectious-recovered (SEIR) model and the basic reproduction was estimated.…”
Section: Introductionmentioning
confidence: 99%